EXPRESSION OF CHITINASE AND -1,3-GLUCANASES IN RICE CULTIVARS IN REACTION TO Rhizoctonia solani,THE CAUSAL AGENT OF RICE SHEATH BLIGHT - SURESH MADUGULA,; PARIMAL K. SINHA, (The Journal of Research ANGRAU, 2023)
Fifteen high yielding rice cultivars were screened for their reaction to sheath blight under field as well as semi-controlled conditions inoculated with the pathogen Rhizoctonia solani Kuhn. Expression of two pathogenesis related proteins (PRPs), Chitinase and -1,3-glucanases activities were estimated. Both chitinase and 1,3-glucanase PR proteins activity in terms of specific activity expressed after 72 h of pathogen inoculation was generally higher in tolerant cultivars (NLR 145, MTU 1061, NLR 3238, MTU 1153) including checks (TETEP and MTU 1001) as compared to control (MTU 7029) and other susceptible cultivars. The presence of a 33 kDachitinase and 32 kDa and -1,3-glucanase proteins was revealed by western blot analysis, across all the rice cultivars following Rhizoctonia solani infection. No significant grain yield difference in relation to the expression of PRPs was observed across the test rice cultivars.